Effect of Tube Spacing, Fin Density and Reynolds Number on Overall Heat Transfer Rate for In-line Configuration - Tahseen, Tahseen Ahmad; M. M., Rahman; M., Ishak (Universiti Malaysia Pahang, 2015)
This paper presents variation of overall d imensionless heat transfer rate against dimensionless tubes spacing, fins density, Reynolds number for in - line configuration. Influence of Reynolds number on the predicted and experimental results of dimensionless pumping power minimization for with respect to the dimensionless fins density for several tube – to – tube spacing also investiga ted. The experiments were conducted at a flat tube in the flow direction, and Reynolds number based on the hydraulic diameter ( Re Dh ) was considered. The dimensionless overall heat transfer rate is always increases with an increase of the Reynolds number. The dimensionless fins spacing effect on the dimensionless overall heat transfer rate increase is noticeable at high Reynolds numbers. The dimensionless pumping power increases with increasing response Reynolds numbers for dimensionless tubes spacing and d imensionless fins density. The dimensionless pumping power decreased with increase of dimensionless fin density